2017
DOI: 10.1016/j.crvi.2017.11.003
|View full text |Cite
|
Sign up to set email alerts
|

Integrating marker-assisted background analysis with foreground selection for pyramiding bacterial blight resistance genes into Basmati rice

Abstract: Bacterial leaf blight (BB), caused by the bacterium Xanthomonas oryzae pv. Oryzae (Xoo), is the major constraint amongst rice diseases in India. CSR-30 is a very popular high-yielding, salt-tolerant Basmati variety widely grown in Haryana, India, but highly susceptible to BB. In the present study, we have successfully introgressed three BB resistance genes (Xa21, xa13 and xa5) from BB-resistant donor variety IRBB-60 into the BB-susceptible Basmati variety CSR-30 through marker-assisted selection (MAS) exercise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 33 publications
(49 reference statements)
0
12
0
Order By: Relevance
“…Compared with traditional breeding strategies, MAS can significantly improve selection efficiency; however, pyramiding multiple genes still requires many generations (Jiang et al 2012;Baliyan et al 2018). In this study, using multiple breeding strategies (single cross, mutual intercross, and backcross) combined with MAS, we successfully obtained BC 1 F 1-7 lines carrying Pita/pita, Pib/pib, and Pid2/pid2.…”
Section: Discussionmentioning
confidence: 99%
“…Compared with traditional breeding strategies, MAS can significantly improve selection efficiency; however, pyramiding multiple genes still requires many generations (Jiang et al 2012;Baliyan et al 2018). In this study, using multiple breeding strategies (single cross, mutual intercross, and backcross) combined with MAS, we successfully obtained BC 1 F 1-7 lines carrying Pita/pita, Pib/pib, and Pid2/pid2.…”
Section: Discussionmentioning
confidence: 99%
“…Compared with traditional breeding strategies, MAS can signi cantly improve selection e ciency; however, pyramiding multiple genes still requires many generations (Jiang et al 2012;Baliyan et al 2018). In this study, using multiple breeding strategies (single cross, mutual intercross, and backcross) combined with MAS, we successfully obtained BC 1 F 1-7 lines carrying Pita/pita, Pib/pib and Pid2/pid2.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, another nine polymorphic SSR and EST-SSR markers reported to be related to other putative protein functions and unknown functions were located on LGs 1, 2, 4 and 5 (Isemura et al ., 2012; Chen et al ., 2015). The number of polymorphic SSR and EST-SSR markers obtained from this study may be lower than those in other studies, which have reported using 26–241 polymorphic loci for background selection (Divya et al ., 2014; Miah et al ., 2015; Pradhan et al ., 2015; Ahmed et al ., 2016; Arunakumari et al ., 2016; Xiao et al ., 2016; Krishna et al ., 2017; Yadawad et al ., 2017; Baliyan et al ., 2018; Jamaloddin et al ., 2020; Kumar et al ., 2021). These results may be due to the number of markers and genetic variation of the parents used.…”
Section: Discussionmentioning
confidence: 99%